2005
DOI: 10.1093/humrep/deh635
|View full text |Cite
|
Sign up to set email alerts
|

Association of FMR1 repeat size with ovarian dysfunction

Abstract: We found a significant positive association of repeat size with ovarian dysfunction, but have preliminary evidence that this relationship is non-linear. We suggest that FMR1 repeat size in the lower range (<80 repeats) contributes to the variation in age at menopause; thus, FMR1 could be considered a quantitative trait locus. More importantly, when repeat size exceeds this threshold, the increase in risk for ovarian dysfunction is clinically significant. Intriguingly, this risk appears to plateau, or perhaps d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
371
4
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(408 citation statements)
references
References 25 publications
25
371
4
5
Order By: Relevance
“…The interesting fact about this finding is that it has also been reported for ovarian insufficiency [21][22][23][24].…”
Section: Neuropsychiatric and Muscular Involvementsupporting
confidence: 63%
See 1 more Smart Citation
“…The interesting fact about this finding is that it has also been reported for ovarian insufficiency [21][22][23][24].…”
Section: Neuropsychiatric and Muscular Involvementsupporting
confidence: 63%
“…It has been found that the risk of POI and the ovarian manifestations present on a specific patient may have a non-linear association with the number of CGG repeats, with the risk of developing ovarian insufficiency increasing with the number of repeats and then reaching a plateau or even decreasing after 80-100 CGG repeats are reached [21][22][23][24]. Allen et al (2007) [24] did a study with 948 carriers with varying repeat sizes in order to get a better view of the reproductive aging milestones among these women and its relation with the number of CGG repeats present.…”
Section: Reproductive Involvementmentioning
confidence: 99%
“…Roughly 20% of female Fmr1 premutation carriers develop a condition known as premature ovarian failure (POF; Sherman, 2000). The disorder is characterized by earlier menopause in premutation carriers compared to non-carriers (Murray et al, 2000;Hundscheid et al, 2001) and risk for POF significantly increases if the CGG repeat size exceeds 80 repeats (Sullivan et al, 2005). In contrast, the risk of developing POF in women without the premutation allele (non-carriers) is only 1% (Murray et al, 2000).…”
Section: The Fragile X Mental Retardation Gene and Proteinmentioning
confidence: 99%
“…A link has been suggested between pituitary inclusions and dysregulated neuroendocrine function in patients with FXTAS. Increased Follicle Stimulating Hormone (FSH) (Hundscheid et al, 2001;Sullivan et al, 2005;Greco et al, 2007) and decreased inhibin A and B levels in female PM carriers were reported even in those who are cycling normally, suggestive of early ovarian aging and ovarian compromise (Welt et al, 2004). Elevated levels of FSH have been found to reflect decreasing ovarian reserve (MacNaughton et al, 1992), which can be correlated to the risk of developing POF seen in female PM carriers.…”
Section: Introductionmentioning
confidence: 99%